Dynamic Electrical Subject for Senior High School: Developing Interactive Tutorial Method Animation - Ardimas Ardimas; Abd Basith; Rendy Priyasmika; Jhelang Annovasho; Norma Sidik Risdianto (Online Learning In Educational Research (OLER), 2021)
In recent years the need for digital technology in various fields is in great demand, including in education fields. This is due to digital technology which makes it easier for students to understand the material and increase learning interest. To increase students' understanding and interest in learning about dynamic electrical material, the Interactive Tutorial Method Animation (ITMA) was developed using Adobe Flash Professional CS6. This research was conducted at the SMA (Senior High School) Laboratory at Islamic University Sunan Kalijaga, Yogyakarta. This model refers to the elaboration research procedure by Borg and Gall. Data were collected using a questionnaire instrument which contained: validation, response, and assessment sheets. Qualitative assessment data from 7 experts on ITMA quality were used as a reference for initial product revisions. Then the qualitative data of student responses were determined using the Guttman statement scale. Ideal percentage and agreement were used to analyze the data of preliminary and main fields, respectively. The results of the experts' evaluation showed very good results, each of which was 92.8% for the material aspect, 91.6% for the media aspect, and 95.2% for the learning aspect. The final product of ITMA received a good response from students with a 96% approval rate. Therefore, it is suggested that the development of ITMA has increased students interest in dynamic electricity subject.